THE RELEVANCE OF STUDYING ASTRONOMY IN ISLAMIC UNIVERSITIES OF NIGERIA WITH PARTICULAR REFERENCE TO AL-QALAM UNIVERSITY, KATSINA - Ladan, Suleiman Iguda (European Scientific Journal, ESJ, 2015)
Astronomy is a science that studies the heavens in an effort to understand the underlying principles governing the behaviour of planets, stars, galaxies and the universe in general. The research is both empirical and theoretical in nature since both primary and secondary sources of data were collected and analyzed in writing the paper The results identified the Islamic Universities of Nigeria and their progrmmes of study The results further identified the place of astronomy in one of the Islamic universities ss just a topic among the six topics that comprise the general studies course unit instead of a full pledge programme. Studying Astronomy has relevance to the Islamic universities because an understanding of the discipline is essential for the appreciation of the religion of Islam, Astronomy enables a Muslim to appreciates the oneness of Allah, the knowledge of Astronomy can be used to effectively served Islam, Islam in general invites man to the study and understanding of the universe. Studying Astronomy in the Islamic universities has prospects as it will assist in resolving disputes associated with moon sighting for the months of Ramadan and Shawwal, many students have shown interest in studying Astronomy among others. There are however certain challenges such as funding of the Islamic universities, very expensive instruments and equipments used in Astronomy that should be overcome for astronomy to be among the programmes to be studied in Islamic universities of Nigeria.